2022
DOI: 10.1002/aisy.202200145
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Demonstration of Multilevel Resistive Random Access Memory Programming for up to Two Months Stable Neural Networks Inference Accuracy

Abstract: Crossbars of resistive memories, or memristors, provide a road to reduce the energy consumption of artificial neural networks, by naturally implementing multiply accumulate operations, their most basic calculations. However, a major challenge of implementing robust hardware neural networks is the conductance instability over time of resistive memories, due to the local recombination of oxygen vacancies. This effect causes resistive memory‐based neural networks to rapidly lose accuracy, an issue that is sometim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…The model of the noise is derived by conductance measurements of our programmed RRAM devices after a relaxation period (Fig. 2 f) and set to 10% of the maximum conductance value in the layer 59 . This approach makes sure that the obtained simulation weights can be mappable on devices with minimal accuracy drop after realistic programming stochasticity and device relaxation effects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The model of the noise is derived by conductance measurements of our programmed RRAM devices after a relaxation period (Fig. 2 f) and set to 10% of the maximum conductance value in the layer 59 . This approach makes sure that the obtained simulation weights can be mappable on devices with minimal accuracy drop after realistic programming stochasticity and device relaxation effects.…”
Section: Resultsmentioning
confidence: 99%
“…Smart programming of the devices can be reached to obtain more precise conductance levels and stabilize the devices with respect to the filament relaxation resulting in a conductance shift 57 , 59 .…”
Section: Methodsmentioning
confidence: 99%
“…(B) Confusion matrix obtained at the end of the training process. (C) Network accuracy, as a function of the time elapsed from the parameter storage, due to the drift mechanism of the assumed memristive synaptic weight physical support (model derived from Esmanhotto et al, 2022 ).…”
Section: Test Casesmentioning
confidence: 99%
“…We here illustrate how the network accuracy may change, assuming the drift of a memristive memory device serving as the physical support of the synaptic weight. We use the circuit design and experimental data presented in Esmanhotto et al (2022) to derive a drift compact model (more details on the drift model are found in Supplementary material (Section 4)). We updated the synaptic model introducing this mechanism, and we simulated the inference on the test dataset as a function varying the time elapsed from an assumed network parameter storage carried out in a write-verify schema (thus, not reliant on any weight quantization).…”
Section: Test Casesmentioning
confidence: 99%
“…over time, due to the local recombination of oxygen vacancies and structural relaxation of the material, respectively 36,37 .…”
Section: Filamentary Memristor and Phase-change Memory As Normal Dist...mentioning
confidence: 99%